Pola Peresepan Obat Antibiotik pada Pasien Poli Gigi RSUD Kajen Kabupaten Pekalongan Tahun 2013 - Sa'adah, Vina Fitri, drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K), drg. Gunawan Sri Sarjono (2015)
Irrational use of antibiotics can cause negative effects such as side effect, unnecessary toxicity, accelerate the occurrence of resistance, widespread infection by resistant germs. Many previous studies found that 40-62% of improper antibiotics usage was applied on the diseases which didn't need it. This study was conducted to find out the rationality of antibiotics prescription towards dental patient at Kajen Regional Public Hospital, Pekalongan on 2013. This is a descriptive observation study with cross sectional approach. The medical records retrospectively used as secondary data. The sample was determined using saturated sampling method. Rationality score was observed according to Gyssens criteria. Using Gyssens criteria, the data could be categorized as follow: about 53.8% of antibiotic prescriptions were appropriate / rational (0 criteria); 6.5% of them were not rational because of improper dosing interval (IIB criteria); 22.3% were irrational because there were other less toxic antibiotics (IVB criteria); 17.4% of them were irrational because there were other cheaper antibiotics (IVC criteria). From the data above we believe that there were irrational antibiotic prescriptions toward dental patient at Kajen Regional Public Hospital, Pekalongan.